Pengaruh Citra Merek, Lokasi, Harga, dan Kualitas Pelayanan terhadap Minat Beli melalui Kepercayaan Konsumen sebagai Variabel Pemediasi - Gregorius Zalukhu; Deya; Mamis Waruwu; Fajar Nurcahyo; Puri Swastika Gusti Krisna Dewi; Meidy Frenky Lombogia (CAPITAL: Jurnal Ekonomi dan Manajemen, 2026)
This study analyzes the influence of brand image, location, price, and service quality on consumer purchase intention, with consumer trust serving as a mediating variable at Roti Bakar 88 Cafe, GOR Damyati, Tangerang City. The primary research question addresses the extent to which these factors affect purchase intention both directly and indirectly through consumer trust. A quantitative approach with a data analysis process using SmartPLS. The results show that brand image, price, and service quality significantly influence consumer trust, while location does not significantly affect trust, it has a direct influence on purchase intention. In addition, the relationship between consumer trust and purchase intention is proven to be significant, establishing trust as a crucial mediating variable in this model. Price and service quality do not directly influence purchase intention but exert an indirect influence through consumer trust. These findings suggest that building consumer trust is essential for driving consumer purchasing decisions in the culinary sector. Therefore, managers should focus on strengthening brand image and maintaining consistent service quality to increase customer loyalty and purchase intention.